Does "Live high-Train low (and high)" hypoxic training alter running mechanics in elite team-sport players? - Girard, O.; Millet, G. P.; Morin, J.-B.; Brocherie, F. (Journal of Sports Science & Medicine, 2017)
This study aimed to investigate if "Live High-Train Low (and High)" hypoxic training alters constant-velocity running mechanics. While residing under normobaric hypoxia (=14 h·d-1; FiO2 14.5-14.2%) for 14 days, twenty field hockey players performed, in addition to their usual training in normoxia, six sessions (4 × 5 × 5-s maximal sprints; 25 s passive recovery; 5 min rest) under either normobaric hypoxia (FiO2 ~14.5%, n = 9) or normoxia (FiO2 20.9%, n = 11). Before and immediately after the intervention, their running pattern was assessed at 10 and 15 km·h-1 as well as during six 30-s runs at ~20 km·h-1 with 30-s passive recovery on an instrumented motorised treadmill. No clear changes in running kinematics and spring-mass parameters occurred globally either at 10, 15 or ~20 km·h-1, with also no significant time × condition interaction for any parameters (p > 0.14). Independently of the condition, heart rate (all p < 0.05) and ratings of perceived exertion decreased post-intervention (only at 15 km·h-1, p < 0.05). Despite indirect signs for improved psycho-physiological responses, no forthright change in stride mechanical pattern occurred after "Live High-Train Low (and High)" hypoxic training.